Emotional regulation strategies (ER) used by trainees to overcome negative emotions - Butt, Fauzia; Mahboob, Usman; Wajid, Gohar; Khan, Rehan Ahmad (Journal of the Pakistan Medical Association, 2023)
Objectives: To identify the use of different emotion regulation strategies by medical trainees, and to determine the frequency and the predominant pattern of emotional response in emotion-triggering situations. Method: The descriptive cross-sectional study was conducted at 2 public and 1 private medical college in Lahore, Pakistan, from March to September 2019, and comprised postgraduate medical trainees of either gender from all clinical disciplines from years 1-4. Data was collected using a questionnaire based on the Gross theory of emotional regulation and the Situational model of emotion. Emotion regulation strategies included situation selection, situation modification, cognitive change, attention deployment, and response modulation. Data was analysed using SPSS 25. Results: Of the 377 trainees approached, 308(81.69%) participated; 206(67%) females and 102(33%) males. The overall mean age was 27.8+2.91 years. The majority of the trainees were from the Obstetrics and Gynaecology department 133(43.2%) and were in the first year of their training 116(37.7%). The most frequent emotion-triggering situation identified was prolonged working hours 292(95%), and the major emotional response was quietness in 5 out of ten situations (50%). The trainees used greater emotion regulation strategies in sad situations 3.49±1.79 (p<0.01). Trainees managed sad emotions by keeping themselves involved in other activities 152(49%); in anger, they blamed others 124(40.3%); in fear, they opted for suppression of emotions 71(22.7%); in disgust, they preferred avoidance 90(29.2%); and in shock, acceptance was a common strategy 21(12.7%). Conclusion: Postgraduate medical trainees struggled to manage emotions and used maladaptive strategies. Key Words: Emotions, Emotion regulation, Mental health, Emotional skill.